Role of Polyphenols in Alleviating Alzheimer’s Disease: A Review - William Raja, Tharsius Raja; Duraipandiyan, Veeramuthu; Ignacimuthu, Savarimuthu; Janakiraman, Udaiyappan; Packiam, Soosaimanickam M. (Current Medicinal Chemistry, 2023)
Alzheimer’s Disease (AD) is a successive neurodegenerative disorder in the aged population. Many chemicals and phytochemicals are used to treat AD. Polyphenols which occur widely in various fruits, vegetables, beverages, and some other plant sources are gaining importance in AD treatment. Polyphenols comprise various subcategories, such as phenolic acids, lignans, tannins, stilbenes, hydroxybenzoic acid, hydroxycinnamic acid, and flavonoids. These compounds, as sole entities or in combination, can be used for treating AD because they have an abundance of antioxidants that are reported to be effective in free radical scavenging, metal ion chelating, and anti-inflammatory activities. Polyphenols of various plant origins have been studied, and these have been supported by in vitro assays and in vivo studies in rodents. These molecules protect neurons against oxidative stress and deposition of amyloid-β (Aβ) and tau proteins which play a vital role in the pathogenesis of AD. Consumption of wine and other foods rich in polyphenols has a beneficial effect on the neuronal signaling pathways, playing a vital role in shielding neuronal cells from neurodegeneration. Their ability to reduce free radicals and chelate metals are of great advantage. In this review, we highlight the various polyphenols that inhibit neuronal damage and progression of AD while also providing a cure. Some of the polyphenols covered are hesperidin, resveratrol, curcumin, catechin, kaempferol, and quercetin. The mechanisms of the actions of three polyphenols are also elaborated.
Keywords: amyloid-β